2010
DOI: 10.1111/j.1532-950x.2010.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine Laryngoplasty Sutures Undergo Increased Loading During Coughing and Swallowing

Abstract: Swallowing increases laryngoplasty suture force to a greater extent than coughing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…) and blockade of the recurrent laryngeal nerve did not change the force exerted on LP prostheses during swallowing or coughing (Witte et al . ). In conclusion, there is no evidence that residual laryngeal adductor function influences the long‐term degree of LP abduction.…”
Section: Loss Of Arytenoid Abductionmentioning
confidence: 97%
See 2 more Smart Citations
“…) and blockade of the recurrent laryngeal nerve did not change the force exerted on LP prostheses during swallowing or coughing (Witte et al . ). In conclusion, there is no evidence that residual laryngeal adductor function influences the long‐term degree of LP abduction.…”
Section: Loss Of Arytenoid Abductionmentioning
confidence: 97%
“…Witte et al . () have since demonstrated that the force exerted on the LP prosthesis during swallowing was significantly greater than that exerted during coughing and suggested that normal swallowing causes LP abduction loss. Irrespective of cause, it should be accepted that some post operative loss of LP abduction is inevitable in most horses.…”
Section: Loss Of Arytenoid Abductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic loading is a critical step in the mechanical evaluation of materials for prosthetic laryngoplasty. We used a cyclic load comparable to previous reports (25–50 N) for 1,000 cycles to represent the load placed on an implant over the first 24 hours . Distraction distance under cyclic load can be interpreted as a measure of the distance an implant could be expected to loosen when used in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Peak load (N) and maximum slope (N/mm) were recorded (Bluehill ® Software, Instron, Norwood, MA). In Experiment 2, arytenoid cartilages (n=6) and cricoid cartilages (n=3) were subjected to a preload of 25 N, then loaded at 25–50 N for 1,000 cycles . Cyclic loading was applied at a distraction rate of 0.83 mm/s, distraction (mm) to maintain load and mean slope (N/mm) were recorded (Bluehill ® Software).…”
Section: Methodsmentioning
confidence: 99%